2009
DOI: 10.1016/j.econedurev.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of educational choice in occupational gender segregation: Evidence from Trinidad and Tobago

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…In contrast, this paper employs an analytical connection between occupational (or sectoral) and educational segregation indices, which is established via the joint distribution of both characteristics and an associated 'total segregation measure' (with educational and occupational indices being based on the respective marginal distributions of gender types over these two categories). A similar construct with different segregation measures appears in Borghans and Groot (1999), who study the trajectory from educational 'presorting' to observed occupational or sectoral segregation and apply this framework to Dutch data (see also Sookram and Strobl, 2009). However, they use the Karmel-MacLachlan index (1988) as a point of departure, which inhibits some less desirable properties, and entails a somewhat intricate decomposition of the trajectory from educational segregation, over total segregation (via counting 'additional segregation' and correcting for 'reintegration'), to occupational/sectoral segregation (see also Flückiger and Silber (1999, p. 135-137), who additionally discuss a multidimensional extension of the Gini segregation measure).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 96%
“…In contrast, this paper employs an analytical connection between occupational (or sectoral) and educational segregation indices, which is established via the joint distribution of both characteristics and an associated 'total segregation measure' (with educational and occupational indices being based on the respective marginal distributions of gender types over these two categories). A similar construct with different segregation measures appears in Borghans and Groot (1999), who study the trajectory from educational 'presorting' to observed occupational or sectoral segregation and apply this framework to Dutch data (see also Sookram and Strobl, 2009). However, they use the Karmel-MacLachlan index (1988) as a point of departure, which inhibits some less desirable properties, and entails a somewhat intricate decomposition of the trajectory from educational segregation, over total segregation (via counting 'additional segregation' and correcting for 'reintegration'), to occupational/sectoral segregation (see also Flückiger and Silber (1999, p. 135-137), who additionally discuss a multidimensional extension of the Gini segregation measure).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 96%
“…This is the focus of the second research sub-question. For this part of the analysis, this study follows the methodology developed by Borghans and Groot (1999), which was also applied in Sookram and Strobl (2009). ATTs and ITTs with educational attainment levels typical for their own racial group may work in similar occupations, thus compensating for their educational segregation by reintegrating (R).…”
Section: Determining Impact Of Educational Segregation On Occupationamentioning
confidence: 99%
“…Andersen et al, 2009;Bennedsen et al, 2007;Lins et al, 2013;Villalonga and Amit, 2006) and to papers that investigate the impact of labor market conditions and individual characteristics, such as gender and personality traits on occupational choice (see e.g. Anker, 1997;Drost, 2002;Kleinjans, 2010;Polachek, 1981;Robertson and Symons, 1990;Sookram and Strobl, 2009).…”
Section: Introductionmentioning
confidence: 99%